Aerodynamic test results of bicycle helmets in different configurations: Towards a responsive design - Novak, J.; Burton, D.; Crouch, T. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2019)
Within the sport of cycling, aerodynamic efficiency is a fundamental criterion for equipment such as bicycle frames, wheels, clothing and helmets. Emerging technologies continually challenge the rules governing the sport as designers, engineers, sports scientists and athletes attempt to gain the edge on their competition. This study compares three-dimensional (3D) printed bicycle helmet prototypes with three commercially available helmets via aerodynamic testing in a wind tunnel. One 3D printed helmet featured a mechanical mechanism allowing two states of ventilation closure to be examined for aerodynamic efficiency, while the other featured electronically adjustable ventilation openings tested at five different states of ventilation closure. Data were collected using an anthropometrically accurate mannequin sitting atop a bicycle in a road-cycling position. The results found that the mechanically controlled prototype offered a 4.1% increase in overall drag experienced by the mannequin with ventilation in the open position compared to the closed position. The electronic prototype showed an increase in drag as ventilation openings increased through the five states, with an overall difference in drag of 3.7% between closed and the maximum opening. These experimental findings indicate that the responsive helmet prototypes can significantly affect the drag force on a cyclist between their closed and open positions and, when understood as being adaptable using sensors and automated controls, may provide new opportunities to modify athlete performance throughout varying stages of training and competition.